Theories and Approaches of the North and South - Ali Khaefzadeh, Mohammad; Hossein Sadeghi, Seyed (Opción, 2019)
We attempt to explain the term "north and south" and their concepts, and also examine the other relevant terms that have the features and characteristics of the north and south concepts. As a method, we use structural theories including underdevelopment and dependency which in fact illustrate the type and nature of the structure of North-South relations. It is resulted that the efforts done to reach advancement in the South countries have also failed. As conclusion, still some significant problems remain, such as inequalities, global poverty and declining living standards and many of these countries are in a high vulnerability position